Improving residential outdoor space experience in developing countries: Evidence from a housing estate in Nigeria. Issue 1 (31st December 2023) - Ukpong, Edidiong; Akah, Utibe; Agbabiaka, Hafeez
Abstract: This study complemented the debate for a better outdoor residential experience but gave a perspective from a developing country, using Ewet housing estate in Uyo, Akwa Ibom State, Nigeria, as a case study. Combining field observation with a questionnaire, data obtained from 150 houses was analysed using descriptive statistics complemented with regression analysis. The results showed that over 60% of the houses were of high quality, however, they were overshadowed by the surrounding lacklustre open space areas. The visual quality of the organisation of the landscape elements had a very strong positive relationship with contribution to amenity value of the neighbourhood. Preference for outdoor activities with recreation, motivation to beautify the premises, and to have a good setting for the house all appeared as positive factors of poor quality development of a residential site. Non-availability of good site design/lack of specification by the housing authority for site development, and inadequate space and site problems, were found to be the major constraints affecting residential site development. The awareness factor had a strong positive relationship with the quality of site development. The study concluded by suggesting a conceptual foundation for improving the process and quality of residential site development in developing countries.